Self-regulation interventions to reduce consumption of sugar-sweetened beverages in adolescents. (1st October 2016) - Ames, Susan L.; Wurpts, Ingrid C.; Pike, James R.; MacKinnon, David P.; Reynolds, Kim R.; Stacy, Alan W.
Abstract: This study evaluated the efficacy of self-regulation interventions through the use of drink-specific implementation intentions and drink-specific Go/No-Go training tasks as compensatory strategies to modify inhibitory control to reduce intake of sugar-sweetened beverages (SSB). In a between-subjects randomized manipulation of implementation intentions and Go/No-Go training to learn to inhibit sugary drink consumption, 168 adolescents reporting inhibitory control problems over sugary drinks and foods were recruited from high schools in southern California to participate. Analysis of covariance overall test of effects revealed no significant differences between the groups regarding calories consumed, calories from SSBs, grams of sugar consumed from drinks, or the number of unhealthy drinks chosen. However, subsequent contrasts revealed SSB implementation intentions significantly reduced SSB consumption following intervention while controlling for inhibitory control failure and general SSB consumption during observation in a lab setting that provided SSBs and healthy drinks, as well as healthy and unhealthy snacks. Specifically, during post-intervention observation, participants in the sugar-sweetened beverage implementation intentions (SSB-II) conditions consumed significantly fewer calories overall, fewer calories from drinks, and fewer grams of sugar. No effects were found for the drink-specific Go/No-Go training on SSB or calorie consumption. However, participants in SSB-II with an added SSB Go/No-Go training made fewer unhealthy drink choices than those in the other conditions. Implementation intentions may aid individuals with inhibitory (executive control) difficulties by intervening on pre-potent behavioral tendencies, like SSB consumption.